The Forefront of Dentistry—Promising Tech-Innovations and New Treatments. (October 2022) - DaSilva, A.F.; Robinson, M.A.; Shi, W.; McCauley, L.K.
Change in our world is happening quickly. For dentistry, this is no exception, and now is the time to foster new opportunities. Advances in the foundational science of dental, oral, and craniofacial health are expanding and enabling personalized care built on strong discoveries in the fields of microbiology, immunology, and neuroscience. Digital communication through electronic health records, patient portals, and teledentistry is emerging as vital new armamentarium for contemporary dental practice. Wearables linked with smartphone apps are trending to monitor pain levels, postoperative symptoms, wound healing, and home oral health habits. Oral fluid diagnostics are rapidly surfacing for use in diagnostics, drug testing, and hormone detection. Manipulation of the oral microbiome is under investigation for caries management and for potential impact on systemic conditions. Resolving mediators of inflammation are promising for addressing the chronic inflammation that plagues periodontal patients. New imaging modalities paired with digital approaches and 3-dimensional printing are formulating disruptions in the technical aspects of dentistry. Augmented reality and virtual reality are providing great potential as teaching tools for dental students and bear promise for lifelong learning for providers. Optimization of information technology and the incorporation of data science partnered with artificial intelligence and machine learning to improve patient care in a learning health care system approach will benefit large numbers of patients. These are exciting times for our profession, yet we need to navigate these paths carefully. Technology needs to significantly and positively change the experience of those involved (patients, dentists, staff, payors). New technologies need to be backed with solid research and implementation science. Automation should focus on improving care with attention to expanding care to the underserved and not lose the critical human connection that our patients need. There is great potential in the emerging innovations yet also great responsibility to ensure they are evidence based on rigorous science and deployable with equity and sensitivity. Knowledge Transfer Statement: This article discusses innovations in technology and treatments that have enormous potential to revolutionize our dental care, including novel concepts in electronic health records, communication between dentists and patients, biologics around diagnosis and treatment, digital dentistry, and, finally, the real-time optimization of information technology. The early implementation and validation of these innovations can drive down their costs and provide better dental and medical services to all members of our society.